Annotated list of the plants of Kansas : ferns and flowering plants, with maps showing distribution of species - Gates, Frank Caleb, 1887-1955 (Topeka, KS: Printed by Kansas State Printing Plant, W.C. Austin, State Printer, 2015)
The purpose of this publication is to enumerate the ferns and flowering plants that occur in Kansas. This especially desirable as no list has been available for many years; the most recent is a series of maps showing distribution of Kansas specimens in the Kansas State Herbarium, published by Prof. A.S. Hitchcock some 40-odd years ago. Some years later B.B. Smyth projected a complete list, but lived to assemble but a third of it.
Flora of Kansas
Contribution no. 391 from the Department of botany, Kansas State College [i.e. Kansas Agricultural Experiment Station].
Call number: QK161 .G3
Keywords: Botany; Kansas; Flora; Plants; Lists (document genres); Annotations